José Andrés Gallego, El motín de Esquilache, América y Europa, Madrid, Fundación Mapfre Tavera y Consejo Superior de Investigaciones Científicas, 2003, 799 pp - Pelosi, Hebe Carmen (2005)
Fil: Pelosi, Hebe Carmen. Universidad de Madrid; España